IWTomics: testing high-resolution sequence-based ‘Omics’ data at multiple locations and scales - Cremona, Marzia A (Bioinformatics, 2018)
SUMMARY: With increased generation of high-resolution sequence-based ‘Omics’ data, detecting statistically significant effects at different genomic locations and scales has become key to addressing several scientific questions. IWTomics is an R/Bioconductor package (integrated in Galaxy) that, exploiting sophisticated Functional Data Analysis techniques (i.e. statistical techniques that deal with the analysis of curves), allows users to pre-process, visualize and test these data at multiple locations and scales. The package provides a friendly, flexible and complete workflow that can be employed in many genomic and epigenomic applications. AVAILABILITY AND IMPLEMENTATION: IWTomics is freely available at the Bioconductor website (http://bioconductor.org/packages/IWTomics) and on the main Galaxy instance (https://usegalaxy.org/). SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.